2008
DOI: 10.3168/jds.2008-1164
|View full text |Cite
|
Sign up to set email alerts
|

Internal Controls for Quantitative Polymerase Chain Reaction of Swine Mammary Glands During Pregnancy and Lactation

Abstract: High-throughput microarray analysis is an efficient means of obtaining a genome-wide view of transcript profiles across physiological states. However, quantitative PCR (qPCR) remains the chosen method for high-precision mRNA abundance analysis. Essential for reliability of qPCR data is normalization using appropriate internal control genes (ICG), which is now, more than ever before, a fundamental step for accurate gene expression profiling. We mined mammary tissue microarray data on >13,000 genes at -34, -14, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
46
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 16 publications
3
46
1
Order By: Relevance
“…The ability of RT-qPCR to accurately detect changes in gene expression relies upon the selection of stably expressed reference genes. Studies in other species have shown that the expression of commonly used reference genes may vary between physiological and nutritional states and experimental treatments (2,4,19,37). Variation in expression of reference genes may limit the ability to detect and verify changes in expression of target genes, thus reducing the percentage of genes that validate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of RT-qPCR to accurately detect changes in gene expression relies upon the selection of stably expressed reference genes. Studies in other species have shown that the expression of commonly used reference genes may vary between physiological and nutritional states and experimental treatments (2,4,19,37). Variation in expression of reference genes may limit the ability to detect and verify changes in expression of target genes, thus reducing the percentage of genes that validate.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the present study, candidate reference genes were selected from RNA-seq expression data (PRP3, CUL1, SF1, SENP2, and IPO9) and from studies conducted in other species [MRPL39 (4,19,37), EIF6 (4), and ATP1A1 (9,24)]. These genes were evaluated across pooled and individual RNA samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few studies have examined reference genes in porcine cells, tissues and organs (Erkens et al, 2006;Foss et al, 1998;Kuijk et al, 2007;Nygard et al, 2007;Tramontana et al, 2008), and reveal that GAPDH and ACTB, two commonly used reference genes, are not necessarily constitutively expressed. Reference genes for skeletal muscle at different developmental stages in pigs have not yet been studied, however.…”
Section: Introductionmentioning
confidence: 98%
“…Vandesompele et al (2002) described the geNorm software to identify the most stable reference genes in a given set of tissue samples, and to determine the optimal number of genes required for reliable normalization of qRT-PCR data. geNorm has been applied to the identification of reference genes in bovine and swine mammary gland (Bionaz and Loor, 2007;Tramontana et al, 2008), but not in mouse mammary gland.…”
Section: Introductionmentioning
confidence: 99%